Air to muscle O2 delivery during exercise at altitude - Calbet, J. A. L.; Lundby, C. (High Altitude Medicine & Biology, 2009)
Hypoxia-induced hyperventilation is critical to improve blood oxygenation, particularly when the arterial Po2 lies in the steep region of the O2 dissociation curve of the hemoglobin (ODC). Hyperventilation increases alveolar Po2 and, by increasing pH, left shifts the ODC, increasing arterial saturation (Sao2) 6 to 12 percentage units. Pulmonary gas exchange (PGE) is efficient at rest and, hence, the alveolar-arterial Po2 difference (Pao2-Pao2) remains close to 0 to 5mm Hg. The (Pao2-Pao2) increases with exercise duration and intensity and the level of hypoxia. During exercise in hypoxia, diffusion limitation explains most of the additional Pao2-Pao2. With altitude, acclimatization exercise (Pao2-Pao2) is reduced, but does not reach the low values observed in high altitude natives, who possess an exceptionally high DLo2. Convective O2 transport depends on arterial O2 content (Cao2), cardiac output (Q), and muscle blood flow (LBF). During whole-body exercise in severe acute hypoxia and in chronic hypoxia, peak Q and LBF are blunted, contributing to the limitation of maximal oxygen uptake (Vo2max). During small-muscle exercise in hypoxia, PGE is less perturbed, Cao2 is higher, and peak Q and LBF achieve values similar to normoxia. Although the Po2 gradient driving O2 diffusion into the muscles is reduced in hypoxia, similar levels of muscle O2 diffusion are observed during small-mass exercise in chronic hypoxia and in normoxia, indicating that humans have a functional reserve in muscle O2 diffusing capacity, which is likely utilized during exercise in hypoxia. In summary, hypoxia reduces Vo2max because it limits O2 diffusion in the lung.